(untitled) (AMC Journal (Dhangadhi), 2025)
This study investigates the relationship between emotional intelligence (EI) and employee engagement in Nepalese commercial banks. The primary objective was to examine how various dimensions of EI, including self-awareness, self-regulation, motivation, empathy, and social skills, impact employee engagement. A quantitative research design was adopted, employing a non-probability convenience sampling technique. Data were collected from 284 employees working in commercial banks in the Kathmandu Valley using a self-administered questionnaire. Descriptive and inferential statistics, including correlation and regression analysis, were conducted using SPSS version 27. The results indicate that emotional intelligence significantly predicts employee engagement (β = 1.107, p < .001), explaining 59% of the variance. Notably, self-awareness, motivation, and social skills were the strongest contributors to employee engagement. The findings suggest that improving emotional intelligence could enhance employee engagement, leading to better performance in organizational settings. Practical implications include the recommendation for banks to implement EI-focused training programs to boost workforce engagement. Future research should explore additional factors that may influence engagement in different contexts using longitudinal data.